The Cultic Milieu: Oppositional Subcultures in an Age of Globalization - Kaplan, Jeffrey S.; Lööw, Heléne (Rowman & Littlefield Publishers, 2002)
In 1999, a seemingly incongruous collection of protestors converged in Seattle to shut down the meetings of the World Trade Organization. Union leaders, environmentalists dressed as endangered turtles, mainstream Christian clergy, violence-advocating anarchists, gay and lesbian activists, and many other diverse groups came together to protest what they saw as the unfair power of a nondemocratic elite. But how did such strange bedfellows come together? And can their unity continue? In 1972—another period of social upheaval—sociologist Colin Campbell posited a 'cultic milieu': An underground region where true seekers test hidden, forgotten, and forbidden knowledge. Ideas and allegiances within the milieu change as individuals move between loosely organized groups, but the larger milieu persists in opposition to the dominant culture. Jeffrey Kaplan and Helene Loow find Campbell's theory especially useful in coming to grips with the varied oppositional groups of today. While the issues differ, current subcultures often behave in similar ways to deviant groups of the past. The Cultic Milieu brings together scholars looking at racial, religious and environmental oppositional groups as well as looking at the watchdog groups that oppose these groups in turn. While providing fascinating information on their own subjects, each essay contributes to a larger understanding of our present-day cultic milieu. For classes in the social sciences or religious studies, The Cultic Milieu offers a novel way to look at the interactions and ideas of those who fight against the powerful in our global age.